The Intraoperative use of Prophylactic Steroids Therapy on Postoperative Cough for Heavy Smoker Patient Under Elective Extra Thoracic Surgery - Ahmed Yasser Raddad; Ahmed Adil Ahmed; Nazzal Jebur Mzaiel (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Introduction: Anesthesia is a complex pharmacological Response induced by a chemically heterogeneous class of Drugs, the so-called general anesthetics Every year, tens of Millions of patients are exposed to general anesthetics Drugs that remove the most precious human attribute Consciousness. By allowing for prolonged invasive Procedures, general anesthesia is one of the foremost Achievements of modern medical science However, there Is no objective or widely accepted definition of general Anesthesia. Aim of the study: The aim of study uses of prophylactic nebulized steroids therapy on postoperative cough in a heavy smoker patient under elective extra thoracic surgery. Results: The data was analyzed using the statistical program IBM SPSS Statistic 28 the results attached below were obtained based on the following hypotheses and aim of this study (The aim of study use of prophylactic steroids therapy on postoperative cough for heavy smoker patient under elective extra thoracic surgery). Discussion: In this study, it was attempted to determine the effect of steroids therapy on post-operative cough in patients smoking. And there was high-significant data for each drug group. From this data we note that from study questionnaire the use of nebulizer pulmicort which is making less side effect on patients from than using systemic dexamethasone to patients. and be better drug used for patient who have chronic disease such as (hypertension, diabetic mellitus, problem in respiratory system and complication. Conclusion: from all results in this study, we can conclude that there is a significant effect on shortness of breath and high significant data variable effect on cough according to data research.